The 200 m athlete - Settle, L. A. (Techniques Magazine, 2012)
Valuable athletes on the team who can contribute to the championship season are important for every program. Every season, athletes` training cycles are strategically designed to peak at the right moment to optimize team scoring. At the championships, a skilled jumper, a technically sound thrower, and a talented endurance runner can successfully compete in multiple events. This holds true for the properly trained the 200-meter sprinter as well, who could potentially contribute in as many as four events at a championship meet. To date, there is an enormous amount of literature and training methodologies for acceleration, maximum velocity, and the 400-meter sprinter. Despite the multitude of sprint studies and articles, there is a lack of literature specifically for the 200-meter sprinter. The purpose of this article is to describe the phases of the 200 meters and provide recommendations for future development of the event.